(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2022)
In Earth and Environmental Sciences, pressure calcimetry is probably the most efficient and fast method to determine calcium carbonate (CaCO3) content in rocks, sediments and soils. However, measurements of low-CaCO3 samples can be less reliable by calcimetry, depending on the instrument used. This problematic is particularly relevant for sediments and soils with low content of CaCO3, very common in past and present lakes, soils and hydromorphic systems (e.g., peatbogs, mires, wetlands), where CaCO3 analysis contribute to understand water table changes, groundwater oscillation, ecology and wind-related processes, among others. In this context, this work presents a simple protocol to obtain accurate CaCO3 determinations through pressure calcimetry in low-CaCO3 samples (<4%), even though their CaCO3 content falls below the limit of detection of the instruments. Calibration curves were first established with a CaCO3 standard to calculate the critical value, detection limit and quantification limit, using two different pressure calcimeters. By considering these thresholds, a set of four natural samples with low-CaCO3 content were measured by pressure calcimetry and also analyzed by Loss-on-Ignition and micromorphology. Results with 1 g of sample were lower than the detection limit. Accordingly, a gradual increase of sediment mass was applied until obtaining results above the quantification limit. The amount of CaCO3 per g was thus inferred. Both calcimeters showed comparable results and high consistency with micromorphological observations. The CaCO3 content calculated by Loss-on-Ignition showed slightly lower values, likely due to the loss of structural water and dehydroxylation of some minerals exposed to high temperature, affecting calculations of both organic and inorganic carbon.